Students’ Perceptions of Using Ted Talks as a Media to Improving Speaking Skill - Syafrizal, Syafrizal; Syamsun, Tosi Rut (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2023)
This research aimed to describe the students' perceptions of improving speaking skills using TED Talks as a learning media. Qualitative research is implicated in this study with a descriptive approach. The questionnaire was used as the instrument, and ten open-ended questions were allocated to the participants. The participants were English Department students in the sixth semester in precise. Nineteen students filled out the questionnaire. The data were analyzed in descriptive form. The result from the participants through the questionnaire reveals that the participants respond positively to the utilization of TED Talks in improving speaking skills. TED Talks assist students in mastering linguistic competencies. Furthermore, TED Talks help them give impactful and meaningful messages to enhance self-esteem and deal with anxiety when performing in front of audiences.